Faktor-faktor pendorong intensi membeli produk vegan - Brian Jordy; Dwinita Laksmidewi (Universitas Kristen Maranatha, 2022)
Vegetarianism is a healthy lifestyle trend that is growing in recent years. This study aims to analyze the effect of environmental concern, healthy awareness, social influence, animal welfare, and attitude toward consumption as a mediating variable that can influence the purchase intention of vegan products in Jabodetabek. This study took a research sample of 130 vegetarian respondents living in Jabodetabek using the Purposive Sampling technique. The results showed that social influence and animal welfare had a significant effect on the intention to buy vegan products. Attitude toward consumption becomes a significant mediation in the influence of social influence and animal welfare on purchase intention. Meanwhile, environmental concern and healthy awareness have no significant effect on the intention to buy vegan products. And attitude toward consumption cannot be a significant mediation in the influence of environmental concern and healthy awareness on purchase intention. For marketers in the vegan industry, the results of this study have implications for the importance of consumer education regarding the correlation between consumer health and animal welfare with vegan products.